Imperios en el crepúsculo: las relaciones sino-españolas (1864-1912), el nacimiento de un modelo de forma sin fondo - Ramírez-Ruiz, Raúl; Guanjie, Niu (El Colegio de México, 2025)
The relations between China and Spain from their formal establishment in 1864 until the fall of the Qing Dynasty in 1912 are described on the basis of documents about Spain kept by the Qing Ministry of Foreign Affairs in The First Historical Archives of China, which collect di plomatic communications between the Chinese central government and Spanish institutions, as well as Chinese interdepartmental reports focusing on Spain. The relevant dynamics of these relations are identified and characterized as very formal but without deep content. Excessive emphasis has been placed on protocol issues, demonstrating the absolute weakness of the political and economic ties between both countries. For China, Spain was a friendly but irrelevant nation, while for Spain, China was nothing more than a luxury expense, but an affordable one.